Impact of higher education on economic growth: A vector error correction analysis in malawi - Mbewe, Gift (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2024)
This study examined the impact of higher education on economic growth in Malawi from 1995 to 2021. The study contributes to existing literature by providing more recent evidence and as well contributes to the debate on whether higher education has a positive or negative impact on economic growth in a developing country like Malawi. Empirical studies have so far yielded inconclusive results. The time series variables were tested to find out its order of integration using Dickey Fuller and the series were all non-stationary at level but became stationary after first difference. The study employed cointegration and evidence of cointegration of higher education and economic growth was established. However, Vector Error Correction Model estimates showed that there is negative long run relationship between higher education and economic growth. Thus, the government and other relevant education stakeholders should strive to increase enrollment in tertiary institutions so that it yields significant impact on economic output.